BLOCKCHAIN SOLUTION FOR THIRD PARTY ADMINISTRATOR PROCESS IN HEALTH INSURANCE MEDICAL CLAIMS (IITM Journal of Business Studies, 2024)
India has a vast population of 1.3 Billion  people out of which approximately 44% have  a health insurance policy 1. In the FY 2017-18  alone, there were approximately 4.7 million  Indians who claimed mediclaim insurance  for hospitalization done which included both  pre-planned as well as emergency visits to the  hospital 2. Each of these claims took around  4-6 hours of processing and follow-up time  costing hugely to the claimants 3. The objective  of this paper is to evaluate the reduction in Turn  Around Time (TAT) and thereby reduce costs  in terms of man-hours saved by effective use of  Blockchain for the purpose of settling claims. Since Blockchain is a new revolutionary  development in the field of online real-time  processing of data, there have been very few to  Nil studies in this area. Secondary data has been  collected from various sources (please check  References) and analyzed for effective resolution. The evaluation shows that shifting to a Blockchain  based platform for processing medical claims  will go a long way in reducing TAT thereby  saving both time and cost for the average  claimant. Applications: Smart contracts can be  applied to automatically indemnify claimants  when conditions in the policy are met thereby  reducing human intervention in majority of  the cases. Conclusion: Blockchain based claim  processing platform can ensure that most of the  claims are processed on a real time basis.
Keywords: Third Party Administrators; Blockchain; Mediclaim